The Explicit and The Implicit in AlWasti’s Art - Assit. prof. Athmar Hameed Karim; Assit. prof Salah Hadi Bashan (Genius Journals, 2022)
The current research deals with (the explicit and implicit in the art of Al-Wasiti), which proceeds from the reference of the written text to present a visual text different from the literals of the written, according to the ability of the artist’s personal imagination in the process of representation based on the process of understanding, interpretation or special reading that gives his visual text an entity independent from the written by deleting or addition, through a first moment of intertextuality, the visual text expands and it has a completely independent existence, despite its association with the written one, and it remains in place, due to its relationship as a guide to reading it and accompanying it in the linear entity, i.e. its presentation to the reader’s sight at the moment of scanning the linguistic entity of the text.
Keywords: The explicit; the implicit; the plastic art; Al-Wasiti